Development of E-Learning with Schoology in Hybrid Learning Strategy for Listening Skill of Tadulako University - Utami, Aidilla Putri; Florentinus, Totok Sumaryanto; Ahmadi, Farid (Innovative Journal of Curriculum and Educational Technology, 2021)
Schoology is a learning management system that helps in the teaching and learning process at a time when classroom learning is avoided. This study is focused on developing E-learning with Schoology and to find out whether Schoology improves student learning outcomes and listening skills or not. The type of research used is ADDIE from Dick and Carey. Furthermore, the pretest-posttest control group design was used, which was followed by 100 subjects who were taken by purposive sampling technique. Furthermore, the test is used to test learning achievement while exploring listening skills through interviews. Thus, data analysis was carried out quantitatively and qualitatively. After collecting data by experts, it shows that the developed Schoology media gets a score of 86 which means very good, the material gets a score of 95 which means very good and practitioner gets a score of 98 which means very good. It can be concluded that E-Learning in Schoology is valid. Furthermore, the posttest data shows that there is an increase in the experimental class after receiving treatment through Schoology, it can be seen that the final results of the Mann-Whitney test are 0.00> 0.05 for the experimental class. The implication of this article is that it has a positive impact on curriculum development that is centered on developing interactive and easy-to-implement learning media. The use of Schoology in the learning process is very easy, efficient and interactive to apply in the learning process so that it can improve learning outcomes and listening skills.